A Novel Organoid Model of Damage and Repair Identifies HNF4α as a Critical Regulator of Intestinal Epithelial RegenerationSummary - Paula S. Montenegro-Miranda; Jonathan H.M. van der Meer; Christine Jones; Sander Meisner; Jacqueline L.M. Vermeulen; Jan Koster; Manon E. Wildenberg; Jarom Heijmans; Francois Boudreau; Agnes Ribeiro; Gijs R. van den Brink; Vanesa Muncan (Cellular and Molecular Gastroenterology and Hepatology, 2020)
Background & Aims: Recent evidence has suggested that the intact intestinal epithelial barrier protects our body from a range of immune-mediated diseases. The epithelial layer has an impressive ability to reconstitute and repair upon damage and this process of repair increasingly is seen as a therapeutic target. In vitro models to study this process in primary intestinal cells are lacking. Methods: We established and characterized an in vitro model of intestinal damage and repair by applying γ-radiation on small-intestinal organoids. We then used this model to identify novel regulators of intestinal regeneration. Results: We identified hepatocyte nuclear factor 4α (HNF4α) as a pivotal upstream regulator of the intestinal regenerative response. Organoids lacking Hnf4a were not able to propagate in vitro. Importantly, intestinal Hnf4a knock-out mice showed impaired regeneration after whole-body irradiation, confirming intestinal organoids as a valuable alternative to in vivo studies. Conclusions: In conclusion, we established and validated an in vitro damage–repair model and identified HNF4α as a crucial regulator of intestinal regeneration. Transcript profiling: GSE141515 and GSE141518.